APPLICATION OF THE LAW AGAINST VIGILANTES (EIGENRICHTING) WHICH RESULTED IN DEATH (Decision Study No: 2526/pid.B/2022/PN.Mdn) - Hasibuan, Mhd Dandi Parliansyah (Inspiring Law Journal, 2024)
Vigilantism (Eigenrichting) is the act of individuals or groups taking the law into their own hands through violence outside of the legitimate legal process. This practice is often fuelled by disillusionment with the justice system, anger, or a desire for revenge, but leads to human rights violations and severe legal consequences. Therefore, vigilantism must be condemned and resisted. Law enforcement must be conducted through a legitimate and fair process, and everyone must respect the law. This research evaluates the phenomenon of vigilantism in Indonesia. The research conducted is normative legal research with a Normative Juridical approach that uses descriptive analysis with data obtained in the form of data sourced from Islamic law and secondary data supported by tertiary legal materials.The results showed that the regulation of criminal offences in the form of vigilantism according to the Criminal Code is regulated in Article 170, Article 351, Article 406, Article 338 and in the verdict of the act as regulated and punishable in verdict Number 2526/Pid. B/2022/PN.Mdn the perpetrator of the vigilante action was charged with Article 170 paragraph (2) book 3. The qualification of the offence of vigilantism (eigenrichting) that resulted in fatalities in criminal law is that the defendant's actions have fulfilled all the elements of the indictment in Article 170 of the Criminal Code paragraph (2) book 3 so that the panel of judges sentenced the defendant to 10 (ten) years imprisonment. Although the verdict was based on the fulfilment of the elements of the indictment, research states that law enforcement against vigilantism has not yet reflected its effectiveness. In this context, a legal process that is more in line with justice and legal certainty for victims is needed. The research method used is Normative Juridical with secondary data and legal expert interviews. The findings highlight the importance of effective law enforcement against vigilantism that fulfils the elements of Article 170 or 351 of the Criminal Code in order to achieve justice for the defendant as well as the victim